Antecedents of faith integration self-efficacy in PreK-12 Mennonite schools in North America. Issue 1 (2nd January 2022) - Wiens, Peter D.; Hightower, Andromeda; Yoder, Paul J.; Chou, Annie
ABSTRACT: Private Christian schools in North America endeavour to provide an educational experience that integrates religious and academic training for their preK-12 students. The integration of faith and academics has been studied in higher education institutions in North America, but not substantially in preK-12 schools. This study uses the lens of teacher self-efficacy to examine Christian school teachers' confidence to integrate faith into their instructional practices. A survey was conducted that drew responses from 390 educators from 18 Mennonite-affiliated schools across North America. Responses indicated generally high levels of faith integration self-efficacy for all teachers; however, teachers felt least confident in drawing parents into the process. Regression analysis showed that individual factors did predict faith integration self-efficacy. Implications of these findings are discussed.